2023
DOI: 10.1175/jcli-d-22-0464.1
|View full text |Cite
|
Sign up to set email alerts
|

Mean State AMOC Affects AMOC Weakening through Subsurface Warming in the Labrador Sea

Abstract: While most models agree that the Atlantic Meridional Overturning Circulation (AMOC) becomes weaker under greenhouse gas emission and is likely to weaken over the 21st century, they disagree on the projected magnitudes of AMOC weakening. In this work, CMIP6 models with stronger climatological AMOC are shown to project stronger AMOC weakening in both 1 percent ramping CO2 and abrupt CO2 quadrupling simulations. A physical interpretation of this result is developed. For models with stronger mean state AMOC, strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…This weaker AMOC is also reflected in the decreased meridional potential density gradient across the Atlantic Ocean (Figures S3e and S3f in Supporting Information ). The vast expansion of the Arctic sea‐ice pack after AMOC collapse (van Westen et al., 2023) limits the AMOC recovery to about 5 Sv as sea ice strongly suppresses deep water formation (Lin et al., 2023) by limiting air‐sea fluxes (details are discussed in the next subsection). The resulting effect of sea ice is that there is a relatively cold and fresh surface layer near the deep water formation regions at the higher latitudes (Figure S2 in Supporting Information ) and this strongly increases the vertical stratification preventing deep water formation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This weaker AMOC is also reflected in the decreased meridional potential density gradient across the Atlantic Ocean (Figures S3e and S3f in Supporting Information ). The vast expansion of the Arctic sea‐ice pack after AMOC collapse (van Westen et al., 2023) limits the AMOC recovery to about 5 Sv as sea ice strongly suppresses deep water formation (Lin et al., 2023) by limiting air‐sea fluxes (details are discussed in the next subsection). The resulting effect of sea ice is that there is a relatively cold and fresh surface layer near the deep water formation regions at the higher latitudes (Figure S2 in Supporting Information ) and this strongly increases the vertical stratification preventing deep water formation.…”
Section: Resultsmentioning
confidence: 99%
“…We have shown here that the Northern Hemisphere sea‐ice distribution has a substantial effect on the recovery of the AMOC. The fact that sea ice inhibits air‐sea fluxes, and hence convection, is important (Lin et al., 2023) for the recovery of the AMOC in the CESM and hence for the hysteresis width. The sea ice is the main reason for the strong asymmetry in the hysteresis, where the recovery is a factor six faster than the collapse.…”
Section: Discussionmentioning
confidence: 99%
“…One important mechanism controlling AMOC weakening proposed previously by [88] and supported by [13] involves sea ice: models with a greater sea ice extent have greater sea ice retreat as the climate warms and a hence greater increase in area exposed to the atmosphere. This enables more heat loss from the ocean, offsetting the reduction in heat loss from atmospheric warming which is driving the AMOC weakening.…”
Section: Biasesmentioning
confidence: 88%
“…Correlations of sea surface salinity (SSS) in the North Atlantic with the AMOC across several CMIP6 models show similar findings (figure 1 a ). A recent study [13] has also shown that other aspects of the mean state in the Labrador sea are related to AMOC strength: those models participating in CMIP6 that have a stronger mean AMOC strength have a warmer, more saline Labrador sea, with weaker stratification and less sea ice extent. However, it is not clear what the causality of the biases is, since a model with a stronger AMOC might be expected to have a greater northwards transport of heat and salt, resulting in a warmer and more saline Labrador sea, and hence less sea ice and a weaker stratification with deeper convection.…”
Section: Biasesmentioning
confidence: 99%
See 1 more Smart Citation